2003
DOI: 10.5558/tfc79579-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of forest structure among old-growth, variable retention harvested, and clearcut peatland black spruce (Picea mariana) forests in boreal northeastern Ontario

Abstract: Harvesting techniques that retain structural elements of the original forest may help to preserve the characteristic ecological features and biological diversity of old-growth forests. Harvesting with advance regeneration protection (HARP) is one such technique practised in the Lake Abitibi Model Forest of northeastern Ontario on peatland sites. In this system, winter harvesting operations clear trees in strips about 5-7 m wide and using a minimum diameter limit cut extract trees from the adjacent residual for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
3
14
1
1
Order By: Relevance
“…Red-backed voles are known for their high water requirements and their preference for mesic habitats (Getz 1968;Morris 1996). The removal of canopy cover and soil disturbance from harvesting can reduce live moss cover relative to uncut stands (Deans et al 2003), and decreases in vole density following harvesting disturbance have been attributed to reductions in the availability of moist microhabitats (Sullivan et al 2008). Accordingly, the isodar intercept (equal to: b 0 ?…”
Section: Discussionmentioning
confidence: 99%
“…Red-backed voles are known for their high water requirements and their preference for mesic habitats (Getz 1968;Morris 1996). The removal of canopy cover and soil disturbance from harvesting can reduce live moss cover relative to uncut stands (Deans et al 2003), and decreases in vole density following harvesting disturbance have been attributed to reductions in the availability of moist microhabitats (Sullivan et al 2008). Accordingly, the isodar intercept (equal to: b 0 ?…”
Section: Discussionmentioning
confidence: 99%
“…To date, most research examining responses to partial harvesting in the boreal has focussed on biodiversity, specifically looking at how levels of retention affect taxa of conservation or ecological concern, such as small mammals (Moses and Boutin 2001, Fisher and Bradbury 2006), birds (Lance and Phinney 2001, insects (Gandhi et al 2004, Deans et al 2005, Martikainen et al 2006, ectomycorrhizal fungi (Dahlberg et al 2001, Lazaruk et al 2005, understorey plants Vanha-Majamaa 2001, Bradbury 2004), and coarse woody debris, an important habitat substrate (Deans et al 2003, Lilja et al 2005. Most studies find that partial cuts maintain levels of biodiversity higher than those found in clearcuts but lower than those of uncut stands.…”
Section: Introductionmentioning
confidence: 99%
“…Deans et al 2003). This is because the simple creation or preservation of irregular structure does not guarantee that these stands will be used by old-growth specialist species.…”
Section: Management Solutionsmentioning
confidence: 96%